POLA PENGAWASAN UJI KELAYAKAN KENDARAAN BERMOTOR PADA DINAS PERHUBUNGAN KABUPATEN KONAWE UTARA - Jopang; Wa Ode Harliyanti Unga; La Ode Efrianto; Rosika; Yusnita (Journal Publicuho, 2022)
The purpose of this study was to analyze the pattern of oversight of the due diligence of motorized vehicles at the North Konawe Regency Transportation Service. This study used a descriptive qualitative approach with 8 informants. The determination of informants was carried out using a purposive technique. The research data was obtained through desk studies, interviews and document studies. The data obtained is then analyzed qualitatively with an interactive model and continues continuously until the data is saturated, starting from data collection, data reduction, data presentation and conclusions. The results of the study show that the monitoring pattern for the due diligence of motorized vehicles at the North Konawe District Transportation Service has not been implemented properly. This is due to the absence of a motorized vehicle testing center at the North Konawe District Transportation Service. Testing the feasibility of motorized vehicles is carried out at the Kendari City Motor Vehicle Testing Center UPTD. However, the North Konawe Regency Transportation Service through the Traffic Sector which is carried out operationally by the traffic monitoring and control section carries out a direct supervision pattern for consumers by ensuring that vehicles that will be tested must obtain a recommendation, registration and test number from the North Konawe Regency Transportation Service . Indirect supervision by requesting test results documents and complaints about vehicle testing problems before and after testing.